International financial statement analysis - Robinson, Thomas R.; Greuning, Hennie V.; Henry, Elaine; Broihahn, Michael A. (Hoboken, N.J. : John Wiley & Sons, 2009)
This book is a practical oriented introduction to financial statement analysis.
Foreword by Sir david tweedie, chairman, international accounting standards board.
Includes bibliographical references (p. 803-805) and index.
aia 09/05/13
Loan
Keywords: Financial statements; International business enterprises